Capital, interrupted : agrarian development and the politics of work in India - Gidwani, Vinay K., 1965- (University of Minnesota Press, 2008)
The central Gujarat region of western India is home to the entrepreneurial landowning Patel caste who have leveraged their rural dominance to become a powerful global diaspora of merchants, industrialists, and professionals. Investigating the Patels intriguing ascent, Vinay Gidwani analyzes its broad implications for the nature of labor and capital worldwide. With the Patels as his central case, Gidwani interrogates established concepts of value, development, and the relationship between capital and history. Capitalism, he argues, is not a frame of economic organization based on the smooth, co.